Protein folding: a perspective for biology, medicine and biotechnology - Yon,J.M. (2001)
At the present time, protein folding is an extremely active field of research including aspects of biology, chemistry, biochemistry, computer science and physics. The fundamental principles have practical applications in the exploitation of the advances in genome research, in the understanding of different pathologies and in the design of novel proteins with special functions. Although the detailed mechanisms of folding are not completely known, significant advances have been made in the understanding of this complex process through both experimental and theoretical approaches. In this review, the evolution of concepts from Anfinsen's postulate to the "new view" emphasizing the concept of the energy landscape of folding is presented. The main rules of protein folding have been established from in vitro experiments. It has been long accepted that the in vitro refolding process is a good model for understanding the mechanisms by which a nascent polypeptide chain reaches its native conformation in the cellular environment. Indeed, many denatured proteins, even those whose disulfide bridges have been disrupted, are able to refold spontaneously. Although this assumption was challenged by the discovery of molecular chaperones, from the amount of both structural and functional information now available, it has been clearly established that the main rules of protein folding deduced from in vitro experiments are also valid in the cellular environment. This modern view of protein folding permits a better understanding of the aggregation processes that play a role in several pathologies, including those induced by prions and Alzheimer's disease. Drug design and de novo protein design with the aim of creating proteins with novel functions by application of protein folding rules are making significant progress and offer perspectives for practical applications in the development of pharmaceuticals and medical diagnostics.